Discrepancy Analysis of The Implementation of Authentic Assessment in EFL Classroom of Senior High School in Kuta Utara, Badung based on Curriculum 2016. - ., NI LUH PUTU SUASTINI; ., PROF. DR. A.A.ISTRI NGR.MARHAENI,M.A.; ., DR. LUH PUTU ARTINI, M.A. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2017)
TujuanpenelitianiniadalahuntukmenganalisakesenjanganantaraStandarAsesmenOtentikdenganpelaksanaannya di kelas yang menggunakanBahasaInggrissebagaibahasaasing di SMAN 1 Kuta Utara.Penelitianinimenjawabduapertanyaan, 1)Sejauhmanakesenjangan yang terjadidalampelaksanaanAsesmenOtentik n 2) pemahaman guru tentangOtentikAssesmen yang adadalamKurikulum 2013.PenelitianinimenggunakanDiskrepansi Model Provus.Terdapat lima langkahdalam model ini, yaitu; 1) tahapdefinisi, 2)tahapinstalasi, 3) tahap proses, 4) tahapproduksi, dam 5) tahapmanfaatbiaya. Data yang diperolehmencakupPenilaianDiri, PenilaianUnjukKerja,PenilaianProduk, danPenilaianPortofolio. Data diperolehdariobservasikelas, interview, dankuisioner.Data tersebutdiolahdengan PAIT (PedomanAcuan Ideal Teoritic).Kesenjangan yang banyakmunculpadaPenilaianDiri (52.91%) danPenilaianPortofolio (64.64%). Secaraumumkesenjanganynagterjadiadalah 35.22% dengankategori ‘sedang’.Untukpemahaman guru, diperolehnilai 20.99 (sangattinggi).Hal inimenjelaskanbahwa guru memilikipersepsi yangbagusterhadapAsesmenOtentik yang terdapatdalamKurikulum 2013.Akan tetapibanyakkendala yang dihadapi guru dalampelaksanaanya. Prototype penelitianinidikembangkanberdasarkananalisasilabus, observasikelas, interview dankuisioner.Kata Kunci : kesenjangan, penilaian otentik, kurikulum 2013, pemahaman guru This study aimed at analyzing the discrepancy between the ideal Authentic Assessment Standard and the real implementation in EFL Classroom at SMAN 1 Kuta Utara, Badung Regency. There are two research questions in this study; first, to what extend the discrepancy of the implementation of the authentic assessment in SMAN 1 Kuta Utara is, and second, what the teachers’ belief of the authentic assessment based on Curriculum 2014 in SMAN 1 Kuta Utara is. The study was modified by using Provus’ Discrepancy Model. Thesteps comprises are (1) Definition Stage,(2) Instalation Stage, (3) Process Stage, (4) Product Stage, and (5) Cost-Benefit Stage. Thedata which cover Self-Assessment, Performance Assessment, Project Assessment, and Portfolio Assessment were collected through classroom observation, interview, and questionnaire. The data was analyzed by using Analysis Statistic Descriptive and Ideal Theoretical Reference. The results confirm that there are discrepancy occurred in the implementation of Authentic Assessment in SMAN 1 Kuta Utara based on Curriculum 2013. The most discrepancy occurred in Self-Assessment (52.91%) and Portfolio Assessment (64.64%). The general discrepancy found was 35.22%. it is categorized ‘moderate’. The results of the questionnaire which reflects teacher’s belief is 20.99 (very high). It described the teachershave good perception toward the authentic assessment based on Curriculum 2013.However, they found some obstacles to implement them.The prototype of this study was developed based on syllabus analysis, classroom observation, interview and questionnaire. Thus, the implementation should be developed to reach the standard (Curriculum 2014).keyword : discrepancy, authentic assessment, Curriculum 2013, teacher’s belief